Vocabulary learning strategies of form six students of SMK Sungai Tapang, Samarahan / Frankie Subon - Subon, Frankie (2011)
Vocabulary acquisition is one of the important determinants that enables students to be proficient L2 users. Students' vocabulary size is built up through a variety of learning experiences. VL strategies are classified into 'incidental' and intentional' learning strategies that are present in taxonomies of VL learning strategies by Oxford (1990) , Schmitt (1997) , Sökmen (1997) , etc.